Voltammetric determination of fenbendazole in veterinarian formulations - de Oliveira, M. F.; Stradiotto, Nelson Ramos [UNESP] (Elsevier B.V., 2002)
A versatile voltammetric method for quantitative determination of fenbendazole (FBZ) in commercial tablets has been proposed, where direct dissolution of tablets is carried out in 0.1 mol l(-1) tetrabutylamoniun tetrafluorborate containing dimethylformamide solutions. Linear sweep (LSV), square wave (SWV) and differential pulse (DPV) voltammetry techniques were applied to study FBZ at a glassy carbon electrode, exhibiting a well defined irreversible oxidation peak at 1.15 V vs. SCE. This methodology allows a precise quantitative determination of FBZ presenting detection limits of 5.2 x 10(-5) (LSV), 5.0 x 10(-6) (DPV) and 5.0 x 10(-5) mol l(-1) (SWV). (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: fenbendazole; anthelmintic; voltammetric determination